2011
DOI: 10.3174/ajnr.a2425
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by Categorizing or Dichotomizing Continuous Variables Is Inadvisable: An Example from the Natural History of Unruptured Aneurysms

Abstract: SUMMARY:In medical research analyses, continuous variables are often converted into categoric variables by grouping values into Ն2 categories. The simplicity achieved by creating Ն2 artificial groups has a cost: Grouping may create rather than avoid problems. In particular, dichotomization leads to a considerable loss of power and incomplete correction for confounding factors. The use of data-derived "optimal" cut-points can lead to serious bias and should at least be tested on independent observations to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
162
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(169 citation statements)
references
References 31 publications
3
162
0
4
Order By: Relevance
“…17,31,32 Dichotomization makes analysis less cumbersome, but may introduce bias in the study result (eg, misclassification). 33 The current study made use of all information and demonstrated that individuals with lower SPMH (poor or fair) were less likely to have ever had FOBT compared to those with higher perceived mental health (very good or excellent). Looking on up to date screening, however, the difference in FOBT uptake based on one's perceived mental health was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…17,31,32 Dichotomization makes analysis less cumbersome, but may introduce bias in the study result (eg, misclassification). 33 The current study made use of all information and demonstrated that individuals with lower SPMH (poor or fair) were less likely to have ever had FOBT compared to those with higher perceived mental health (very good or excellent). Looking on up to date screening, however, the difference in FOBT uptake based on one's perceived mental health was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Using the WHO categorization for obesity, the categorical model provided the least precise predicted values of ln(CRP) level [7,23]. Making full use of the scale data for BMI, the linear…”
Section: Discussionmentioning
confidence: 99%
“…In the male sub-sample, the otherHispanic group displayed the highest curve when BMI>30. We also found differences in the shape of BMI-ln(CRP) curve and ln(CRP) estimates compared to other models for women and men sub-samples.Using the WHO categorization for obesity, the categorical model provided the least precise predicted values of ln(CRP) level [7,23]. Making full use of the scale data for BMI, the linear model demonstrated advantages over the categorical model.…”
mentioning
confidence: 99%
“…The situation may be further complicated by the use of dichotomization or categorization of continuous variables according to various cutoff values (such as age categorized in decades 2,9 or as Ͼ65 years or Ͻ65 years), 3 a process that allows the production of various, sometimes diverging, results. 25 The reluctance of investigators to acknowledge that a specific hypothesis was post hoc can prevent readers from being cautious in interpreting these findings. These problems can only be prevented by requiring precise specification and publication of detailed protocols of clinical trials.…”
Section: Problems With Subgroup Analysesmentioning
confidence: 99%